Immune-mediated renal injury in diabetic kidney disease: from mechanisms to therapy - Ma, Lingli; Liu, Dianyuan; Yu, Yue; Li, Zimeng; Wang, Qing (Frontiers in Immunology, 2025)
Diabetic kidney disease (DKD) is now recognized as a multifactorial disorder, driven by the interplay of metabolic dysfunction, chronic inflammation, and immune-mediated renal injury. This review comprehensively synthesizes recent advancements in understanding immune dysregulation as a central driver of DKD pathogenesis, integrating molecular mechanisms with emerging therapeutic strategies. Innate immune activation, which includes macrophage polarization and adaptive immune perturbations, exacerbates glomerulosclerosis and interstitial fibrosis through cytokine storms and mitochondrial oxidative stress. Despite clinical guidelines emphasizing glycemic control and renin-angiotensin-aldosterone system (RAAS) inhibition, their limited efficacy in halting immune-mediated tubular atrophy highlights the unmet need for targeted immunotherapies. By connecting mechanistic discoveries to clinical translation, this work establishes a roadmap for the development of immune-centric therapies. Its critical synthesis of multi-omics data, clinical trial evidence, and preclinical models bridges the gap between laboratory discoveries and bedside applications, laying the groundwork for redefining DKD as a treatable immune-metabolic disorder.